Copolymerization of Tapioca Starch Waste through Grafting of Acrylic Acid Monomer with Cerium(IV) Initiator as Super Absorbent Polymer (SAP) Candidate - Tedi Kurniadi; Agus Eko Prasojo; Riyanti Putri; Nurwanto; Rudi Hartono; Atmadi (Indonesian Journal of Chemical Studies, 2025)
Indonesia, one of the world's largest tapioca starch producers, generates abundant cassava starch waste (onggok) that remains underutilized. This study aimed to enhance the value of onggok by synthesizing a superabsorbent polymer (SAP) through graft copolymerization using acrylic acid monomer and cerium(IV) initiator. Grafting was optimized by varying monomer concentrations (10–40% w/w) while maintaining the initiator concentration at 1.70% (w/w) and a reaction temperature of 53 °C. The optimal grafting occurred at 20% monomer concentration, yielding a grafting percentage of 14.83% and a monomer conversion of 74.15%. FTIR analysis showed increased absorbance ratios of –OH to C=O functional groups, confirming successful grafting. SEM images revealed a transformation from granular to porous structures, while DSC analysis demonstrated a shift in gelatinization temperature from 45.91 °C (raw onggok) to 46.69 °C (grafted), and retrogradation temperature from 140.67 °C to 141.67 °C. The water absorption capacity of the grafted copolymer reached 4.2450 g/g (5.20 g total), nearly double that of raw onggok (2.2716 g/g or 3.20 g), confirming its effectiveness as a SAP material.